Acute and Sub-Acute (28-Day) Oral Toxicity Studies of Ethanolic Extract of Celtis Timorensis Leaves in Rodents (Global Journal of Medical Research, 2014)
Abstract not found
Keywords: celtis timorensis; acute toxicity study; subacute toxicity study; rodents; biochemical parameters and hematological parameters